483 CORONARY ATHEROSCLEROSIS PHENOTYPES IN FOCAL AND DIFFUSE DISEASE. (15th December 2022) - Belmonte, Marta; Sakai, Koshiro; Mizukami, Takuya; Leipsic, Jonathon; Sonck, Jeroen; Norgaard, Bjarne L; Ko, Brian; Maeng, Micheal; Jansen, Jesper Moller; Andreini, Daniele; Ohashi, Hirofumi; Shinke, Toshiro; et al.
Abstract: Introduction: The pathophysiological interplay between coronary physiology and plaque characteristics remains poorly understood. Pullback pressure gradient (PPG) is a novel physiological index that discriminates focal from diffuse coronary artery disease (CAD) based on coronary physiology. We aimed to compare plaque characteristics using between atherosclerotic patterns defined by coronary physiology. Methods: Multicenter, prospective, controlled, single-arm study conducted in five countries (NCT03782688). Patients with functionally significant lesions based on invasive fractional flow reserve (FFR<0.80) were included. Subjects underwent coronary computed tomography angiography (CCTA) with quantitative plaque analysis followed by an invasive procedure with optical coherence tomography (OCT) and motorized intracoronary pressure recordings. Fractional flow reserve (FFR) pullback curves were processed to calculate the PPG. The PPG ranges from 0, indicating diffuse disease, to 1, pointing to focal CAD. Focal and diffuse CAD were defined according to the median PPG value. Results: Overall, 117 patients (120 vessels) were included. The mean age was 64±9, 80% were male, and 22% had diabetes (no difference between focal vs. diffuse). Median PPG was 0.66 [0.54, 0.75]. In CCTA analysis, the plaque burden at minimum lumen area was higher in patients with focal CAD (87±8% focal vs. 82±10% diffuse, p=0.003). Calcifications were significantly more prevalent in patients with diffuse CAD (Agatston score per vessel 50 [9, 166] focal vs. 151 [46, 360] diffuse, p=0.019). In OCT plaque analysis, patients with focal CAD had a significantly higher prevalence of circumferential lipid-rich plaque (37% focal vs. 4% diffuse, p=0.001) and thin-cap fibroatheroma (TCFA 47% focal vs. 10% diffuse, p=0.002). High PPG predicted the presence of TCFA with an AUC of 0.73 (95% CI 0.58 to 0.87). PPG and fibrous cap thickness were negatively correlated (r=-0.55, 95% CI -0.74 to -0.28) independently of FFR. Conclusions: Atherosclerotic plaque phenotypes associate with intracoronary hemodynamics. Vessels with focal disease (high PPG) had a higher plaque burden and predominantly lipid-rich plaque with a high prevalence of TCFA, whereas calcifications were the hallmark of vessels with diffuse pressure loss.